Carboxymethyl cellulose/okara protein influencing microstructure, rheological properties and stability of O/W emulsions. (24th December 2020) - Cai, Yongjian; Huang, Lihua; Tao, Xia; Su, Jiaqi; Chen, Bifen; Zhao, Mouming; Zhao, Qiangzhong; Van der Meeren, Paul
Abstract: BACKGROUND: The role of protein–polysaccharide interactions and their mixtures has been a vital factor affecting the formation and stability of food emulsions. Okara protein (OP), which is extracted from the by‐product of soybean processing, has received much attention because of its abundant sources and potential attributes with respect to food formulation. Carboxymethyl cellulose (CMC), a well‐known food‐grade polysaccharide additive, has been widely utilized in the protein–polysaccharide system, whereas, among the proteins, the role of OP has not yet been explored. RESULTS: The present study first assessed the ζ‐potential and hydrodynamic diameter of aqueous mixtures containing OP (1.0 wt%) and CMC (0–0.5 wt%), followed by the investigation of OP‐CMC mixtures stabilized O/W emulsions. As CMC increased, oil droplet size, surface protein adsorption, apparent viscosity and storage modulus increased, whereas the loss tangent decreased. CONCLUSION: CMC resulted in emulsion destabilization compared to emulsions without CMC, whereas a higher concentration of CMC promoted emulsion stability against creaming for emulsions in the presence of CMC. The results provide information with respect to OP and CMC being incorporated into food formulations and also strengthen our understanding of the related mechanism, in addition to facilitating the further utilization of OP. © 2020 Society of Chemical Industry